The dynamic consent of the Cooperative Health Research in South Tyrol (CHRIS) study: broad aim within specific oversight and communication (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In biobanking and genomics research, data and samples are stored for long time and used in further studies, which may not be sufficiently specified or foreseen at the time of the initial consent. The dynamic consent of the CHRIS study integrates broad research aims, specific oversight and governance mechanisms, and continuous communication with participants, and allows nuanced choices to be changed over time. With this paper, we describe the CHRIS dynamic consent, and illustrate, by discussing data sharing and ongoing consent in the CHRIS study, how dynamic consent can actualize an informed consent model that is suitable for biobanking and genomic research.
Keywords: Dynamic consent; biobanking research; oversight; communication